Harvesting nature's bounty: exploring the ethnobotanical landscape of wild edible plants in the Awi Agäw community, Northwestern Ethiopia - Fassil, Amare; Mazengia, Ethiopia; Gebreamanuel, Bekele; Dessie, Yitayih; Kumera, Bulti; Atnkut, Belsti; Mullualem, Destaw; Tsega, Alemu; Van Damme, Patrick (Journal of ethnobiology and ethnomedicine, 2024)
BACKGROUND: Feeding the world's future population while still facing a variety of socioeconomic and climate change scenarios with uncertain outcomes is a key global societal concern that should be addressed in a science-based manner. Ethiopia boasts a great diversity of wild edible plant species (WEPS), but millions of its citizens still suffer from chronic hunger every year. In this context, we here document the use and conservation of WEPS in the Awi Agäw community, Northwestern Ethiopia. METHODS: We performed a cross-sectional study from October 2021 to June 2022. Ethnobotanical and conservation status data were collected via semi-structured interviews, focus group discussions, field walks and market surveys. A total of 374 respondents from three districts (Guangua, Jawi and Ankasha) were purposely selected for the study. Descriptive statistics, including preference rankings, frequencies and direct matrix rankings, were employed for the data analysis. RESULTS: We identified a total of 39 WEPS plant taxa distributed among 26 families and 32 genera. The Moraceae and Rosaceae had the greatest numbers of plants, with five and three species, respectively. The WEPS are regularly consumed in the study area to alleviate hunger. However, threats such as habitat loss, agricultural expansion, deforestation for firewood and other reasons, and pesticide use threaten WEPS availability. CONCLUSION: Therefore, community-based conservation interventions need to be encouraged to safeguard WEPS and associated traditional knowledge. Furthermore, nutritional quality analysis is recommended for the selection of promising WEPS candidates.
Keywords: senioři; Cross-Sectional Studies; Conservation of Natural Resources; Middle Aged; mužské pohlaví; Ethnobotany; jedlé rostliny; průřezové studie; mladý dospělý; Adult; Plants, Edible; Young Adult; zachování přírodních zdrojů; ženské pohlaví; Humans; Etiopie; lidé středního věku; Ethiopia; etnobotanika; dospělí; Female; Aged; lidé; Male